Endovascular coil embolization of a complex aortic arch pseudoaneurysm following arch stenting. Issue 7 (7th August 2019) - Meijs, Timion A.; Krings, Gregor J.; Molenschot, Mirella M. C.; Voskuil, Michiel
Abstract: Pseudoaneurysm formation is a life‐threatening complication of thoracic aortic stenting due to the high risk of rupture. When located in the aortic arch, anatomic features may pose difficulties in choosing the optimal treatment strategy. Here, we describe the first poststenting aortic arch pseudoaneurysm treated by endovascular coil embolization. This approach, which we performed in a multidisciplinary setting, may be a feasible alternative in patients not considered suitable for open repair or stent‐grafting. As an acute pseudoaneurysm may develop and rapidly expand during the first days after aortic stenting, early follow‐up imaging is preferable.